New Fluorometric Method for the Determination of Ketotifen Fumarate Using Continuous Flow Injection Analysis via ISNAG-fluorimeter (Baghdad Science Journal, 2019)
A newly developed analytical method was conducted for the determination of Ketotifen fumarate (KTF) in pharmaceuticals drugs via quenching of continuous fluorescence of 9(10H)-Acridone (ACD). The method was applied using flow injection system of a new homemade ISNAG fluorimeter with fluorescence measurements at ± 90◦ via 2×4 solar cell. The calibration graph was linear in the range of 1-45 mmol/L, with correlation coefficient r = 0.9762 and the limit of detection 29.785 µg/sample from the stepwise dilution for the minimum concentration in the linear dynamic ranged of the calibration graph. The method was successfully applied to the determination of Ketotifen fumarate in two different pharmaceutical drugs. A comparison was made between the newly developed method analysis and the classical method using the standard addition method via the use of individual and paired t-test and F-test. It was noticed that there was no significant difference between the two methods at 95 % confidence level.